An Approach to Home Environment Monitoring of People with Disabilities Through AioT - Fernandes, Anita; Leithardt, Valderi R. Q.; Santana, Juan Francisco de Paz (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2024)
This work presents the proposal for developing an approach based on AIoT (Artificial Intelligence of Things) to assist in the care of people with some kind of disability, in the context of the domestic environment. The goal is to select and evaluate the Machine Learning algorithms that are best suited to monitoring environments, in the context of Assisted Living, as well as the most relevant data collection methodologies, to create a monitoring approach.